(untitled) (Revista Brasileira Multidisciplinar, 2025)
Feeding the world’s population in a nutritious and sustainable way is one of humanity’s greatest challenges. In response to this challenge, Urban and Periurban Agriculture (UPA) emerges as an alternative for supplying food in cities. The objective of this study is to provide an exploratory overview of urban agriculture worldwide, identifying the main elements of the external environment of the UPA sector, following Competitive Intelligence principles. Based on an initial set of keywords, namely "urban agriculture," "vertical farms," "urban farming," and "vertical farming," academic articles were identified on the Google Scholar platform, and news articles related to the external environment of UPA were sourced from Google News. The searches were limited to the period between January 2020 and April 2024. Subsequently, new keywords were explored as necessary to delve deeper into each element of the external environment. The results show that urban agriculture is expanding globally and is practiced in various models, notably community gardens, rooftop gardens, controlled-environment food cultivation, and cellular agriculture.